2018
DOI: 10.3390/cells7060062
|View full text |Cite
|
Sign up to set email alerts
|

Role of the TRPM4 Channel in Cardiovascular Physiology and Pathophysiology

Abstract: The transient receptor potential cation channel subfamily M member 4 (TRPM4) channel influences calcium homeostasis during many physiological activities such as insulin secretion, immune response, respiratory reaction, and cerebral vasoconstriction. This calcium-activated, monovalent, selective cation channel also plays a key role in cardiovascular pathophysiology; for example, a mutation in the TRPM4 channel leads to cardiac conduction disease. Recently, it has been suggested that the TRPM4 channel is also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 143 publications
0
41
0
Order By: Relevance
“…Prime candidates for mediating this mechanism are mechanosensitive ion channels. In cardiac mechano-transduction, where mechanical stimuli are converted into electrical or chemical signals (28,29), Ca 2+ -dependent ion channels, such as transient receptor potential (TRP) channels (16), act as important modulators of intracellular Ca 2+ homeostasis (30) and are thought to be unique biosensors that activate specific pathological LVH signalling pathways (31,32). As a Ca 2+ -and voltage-activated non-selective monovalent cation channel, transient receptor potential cation channel subfamily melastatin 4 (TRPM4) may contribute to an increase in intracellular Ca 2+ concentration by causing membrane depolarization (33), although we and others (40,41,42) have demonstrated that mammalian TRP channels, including TRPM4, are not directly stretch-activated.…”
Section: Introductionmentioning
confidence: 99%
“…Prime candidates for mediating this mechanism are mechanosensitive ion channels. In cardiac mechano-transduction, where mechanical stimuli are converted into electrical or chemical signals (28,29), Ca 2+ -dependent ion channels, such as transient receptor potential (TRP) channels (16), act as important modulators of intracellular Ca 2+ homeostasis (30) and are thought to be unique biosensors that activate specific pathological LVH signalling pathways (31,32). As a Ca 2+ -and voltage-activated non-selective monovalent cation channel, transient receptor potential cation channel subfamily melastatin 4 (TRPM4) may contribute to an increase in intracellular Ca 2+ concentration by causing membrane depolarization (33), although we and others (40,41,42) have demonstrated that mammalian TRP channels, including TRPM4, are not directly stretch-activated.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, future studies to discern possible mechanisms and to determine the level and other partners in the Trpm4-Na V 1.5 interactions are warranted. The importance of TRPM4 in cardiac electrical activity is highlighted by mutations in its gene linked to conduction disorders such as right bundle branch block, Brugada syndrome, and atrio-ventricular block [24,40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed the hypothesis that TRPM4 may functionally affect the activity of other cardiac ion channels, such as the main cardiac voltage-gated Na + channel Na V 1.5 [12,24]. Since TRPM4 carries an inward current close to resting membrane potential and an outward current at depolarized potentials, increasing or decreasing TRPM4 expression may critically influence the availability of Na V 1.5 channels.…”
Section: Deletion Of Trpm4 Alters the Function And Expression Of Na Vmentioning
confidence: 99%
“…Therefore, TRPM4 may provide a better option to therapeutically target Ca 2+ mishandling. Interestingly, despite the upregulation of TRPM4 in failing human hearts, the channel itself is impermeable to Ca 2+ ; however, it is both Ca 2+ - and voltage-activated ( Nilius et al, 2003 , 2005 ; Wang et al, 2018 ). TRMP4 expression is upregulated by 50-fold in spontaneously hypertensive rats when compared to controls ( Guinamard et al, 2006 ).…”
Section: Calcium Handling Proteins In Cardiac Hypertrophy and Hf Andmentioning
confidence: 99%